Non-Hodgkin's Lymphoma in Thyroid Gland - Roshed, Md. Mahabubur; Ahsan, Sk. Manowar; Rashed, Kazi Abu (Journal of Medicine, 2013)
A rare case of primary non-Hodgkins Lymphoma in a 52-year-old female presented with a large mass in the right lobe of thyroid. The diagnosis was established by fine needle aspiration cytology (FNAC) followed by surgery and finally confirmed by histopathology. DOI: http://dx.doi.org/10.3329/jom.v14i1.14584 J MEDICINE 2013; 14 : 83-84